PENGEMBANGAN SISTEM INFORMASI DESA PAGELAK MADUKARA BERBASIS WEB - Ardias, Asril Lintang; Astrianty, Ledy Elsera (Universitas Trunojoyo Madura, 2024)
In the rapidly advancing digital era, the use of information technology has become increasingly important in improving administrative management and public services, including at the village level. However, in Pagelak Village, administrative processes such as letter creation and complaint handling are still conducted manually, requiring residents to visit and queue at the village office. This leads to inefficiencies, particularly in terms of the time required to complete administrative tasks. Therefore, the aim of this research is to design and develop a web-based village information system that can improve efficiency in administrative processes and public services. The developed system includes important features such as population data management, correspondence services, and community complaint management. Data sources for this research were obtained from literature studies, direct observations, and interviews with village officials and residents. The research method includes problem identification, data collection stages, system analysis and design, system implementation, and system testing. This study produces a web-based village information system for Pagelak Village that helps reduce queues, waiting times, and improves responsiveness in handling complaints. Testing the system using the Black Box method, which includes 14 points, yielded a 100% result, indicating that the system functions well. The implementation results show that the village information system has improved the efficiency and effectiveness of village administration services, thereby contributing to the enhancement of public service quality in Pagelak Village.Keywords: Public Service Administration, Web-Based, Pagelak Village, Information System